Detection of a Potential New Bartonella Species "Candidatus Bartonella rondoniensis" in Human Biting Kissing Bugs (Reduviidae; Triatominae). - Maureen Laroche; Jean-Michel Berenger; Oleg Mediannikov; Didier Raoult; Philippe Parola (Public Library of Science (PLoS), 2017)
BACKGROUND:Among the Reduviidae family, triatomines are giant blood-sucking bugs. They are well known in Central and South America where they transmit Trypanosoma cruzi to mammals, including humans, through their feces. This parasitic protozoan is the causative agent of Chagas disease, a major public health issue in endemic areas. Because of the medical and economic impact of Chagas disease, the presence of other arthropod-borne pathogens in triatomines was rarely investigated. METHODOLOGY/PRINCIPAL FINDINGS:In this study, seven triatomines species involved in the transmission of T. cruzi were molecularly screened for the presence of known pathogens generally associated with arthropods, such as Rickettsia, Bartonella, Anaplasmataceae, Borrelia species and Coxiella burnetii. Of all included triatomine species, only Eratyrus mucronatus specimens tested positive for Bartonella species for 56% of tested samples. A new genotype of Bartonella spp. was detected in 13/23 Eratyrus mucronatus specimens, an important vector of T. cruzi to humans. This bacterium was further characterized by sequencing fragments of the ftsZ, gltA and rpoB genes. Depending on the targeted gene, this agent shares 84% to 91% of identity with B. bacilliformis, the agent of Carrion's disease, a deadly sandfly-borne infectious disease endemic in South America. It is also closely related to animal pathogens such as B. bovis and B. chomelii. CONCLUSIONS:As E. mucronatus is an invasive species that occasionally feeds on humans, the presence of potentially pathogenic Bartonella-infected bugs could present another risk for human health, along with the T. cruzi issue.